2008
DOI: 10.1007/s11802-008-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the lower level of the PBL associated with the Yellow Sea fog-new observations by L-band radar

Abstract: The Chinese east coastal areas and marginal seas are foggy regions. The development of effective forecasting methods rests upon a comprehensive knowledge of the fog phenomena. This study provides new observations associated with the sea fogs over the northwestern Yellow Sea by means of L-band radar soundings with a high vertical resolution of 30 m. The monthly temperature lapse rate, the Richardson Numbers, and the humidity show obvious seasonal variations in the lower level of the planetary boundary layer (PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Remarkably, the simulated seasonal mean profiles at the grids near the two stations are very close to those in observations. Although some differences in inversion strength, the features of both the increase in inversion layer height and the decrease in inversion strength from Cheju to Naze in the simulation period is well reproduced, which is also consistent with the observed climatological distribution (Liu et al, 2016; Zhang et al, 2008; Zhang et al, 2009).…”
Section: Resultssupporting
confidence: 86%
“…Remarkably, the simulated seasonal mean profiles at the grids near the two stations are very close to those in observations. Although some differences in inversion strength, the features of both the increase in inversion layer height and the decrease in inversion strength from Cheju to Naze in the simulation period is well reproduced, which is also consistent with the observed climatological distribution (Liu et al, 2016; Zhang et al, 2008; Zhang et al, 2009).…”
Section: Resultssupporting
confidence: 86%
“…The vertical development of sea fog layer is highly correlated with the atmospheric stratification near the fog top (Zhang et al, ). To identify the observed stratification within the sea fog layer, two stations where sea fog occurred, DFH2 and CS, are selected (Figures a–d).…”
Section: Improvements Of Sea Fog Simulation Caused By the Top‐driven mentioning
confidence: 99%
“…We used codes 46 and 47 to represent the existence of fog (Table 1). The dissipation stage of fog was excluded since the synoptic condition may be changed (Zhang et al, 2008;Guo et al, 2015). The study area covers 171 °W-130 °W, 39 °N-55 °N with a total of 42242 reported fog points (defined as fog cases).…”
Section: Data and Methods 21 Datamentioning
confidence: 99%
“…Turbulence plays an important role in the formation of fog (Koračin et al, 2005;Guo et al, 2015;Huang et al, 2015). The bulk Richardson number (Ri) can be used as a measure of Frontiers in Earth Science frontiersin.org turbulence (Zhang et al, 2008;Huang et al, 2011;Kim and Yum, 2012):…”
Section: Methodsmentioning
confidence: 99%